The influence of numeracy skills on students’ mathematics learning outcomes in the area of plane shapes material at elementary schools in labuan district - Maisaroh; Mustamin Idris; Fajriani; Bakri M (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigated the effect of numeracy skills on mathematics learning outcomes, specifically in the area of 2 plane figures, among 61 fifth-grade students in Labuan Regency. Using a quantitative correlational design, descriptive results showed that students' numeracy skills were in the good category (average 75.90) and learning outcomes were in the fair category (average 70.33). The Spearman rank correlation test showed a positive and significant effect, but the relationship was weak (r = 0.292; p = 0.023 < 0.05). These findings confirm that better numeracy skills contribute to higher learning outcomes, but the weak correlation underscores the important role of other factors (e.g., teaching methods, motivation). This study implies that teachers should optimize contextual numeracy-based learning to improve achievement, especially for complex concepts such as the area of a trapezoid.